1965
DOI: 10.2134/agronj1965.00021962005700030006x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Cutting on the Growth of Creeping Bentgrass (Agrostis palustris Huds.) Roots1

Abstract: Synopsis The rate of growth of individual roots and total root production of creeping bentgrass was significantly reduced at 90° F. Cessation of growth of individual roots occurred more rapidly as temperature was increased from 60° to 90° F., but the rate of root growth on a per day basis was similar in the 60 to 80° F. range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1966
1966
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…Root fresh weight and specific root length of L‐93 were higher than those of Penncross, indicating that L‐93 had greater volume and surface areas of roots in contact with the soil, which could facilitate water and nutrient uptakes under heat stress. An extensive root system would facilitate increase transpirational cooling and, therefore, affect heat tolerance (Beard and Daniel, 1966; Engelke, 1985; Kolb and Robberecht, 1996; Xu and Huang, 2000a). Engelke (1985) reported that creeping bentgrass cultivars that produce more roots and deeper roots were better able to survive intensive heat because they could use more of the soil moisture reservoir for transpirational cooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root fresh weight and specific root length of L‐93 were higher than those of Penncross, indicating that L‐93 had greater volume and surface areas of roots in contact with the soil, which could facilitate water and nutrient uptakes under heat stress. An extensive root system would facilitate increase transpirational cooling and, therefore, affect heat tolerance (Beard and Daniel, 1966; Engelke, 1985; Kolb and Robberecht, 1996; Xu and Huang, 2000a). Engelke (1985) reported that creeping bentgrass cultivars that produce more roots and deeper roots were better able to survive intensive heat because they could use more of the soil moisture reservoir for transpirational cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Wu and Huff (1983) demonstrated that heat tolerant creeping bentgrass clones had a higher root‐to‐shoot ratio and smaller leaf area and thinner stolons compared with heat sensitive clones. Root growth also is positively associated with the performance of creeping bentgrass during summer because an extensive root system facilitates water uptake, increase transpirational cooling, and therefore affects heat tolerance (Beard and Daniel, 1966; Engelke, 1985; Kolb and Robberecht, 1996).…”
mentioning
confidence: 99%
“…The effects of successive defoliations appear to be cumulative. Cessation or retardation of root elongation and root death may occur (Parker and Sampson 1931;Robertson 1933;Peralta 1935;Weaver and Zink 1946;Butler, Greenwood, and Soper 1959;Beard and Daniel 1965;Davidson and Milthorpe 1966). Roots of defoliated plants may be thinner than those of undefoliated plants (Robertson 1933;Biswell and Weaver 1933;Peralta 1935;Beard and Daniel 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant enzymes including SOD, CATs, POD, and APX scavenge active oxygen species to protect plant cells. although other factors such as high or low soil moisture, high humidity, and disease infection also contribute to Despite the importance of the antioxidant system in this problem (Beard and Daniel, 1965; stress tolerance, few studies have characterized the sea-1998a, 1998b). In turn, CAT, POD, and temperatures increase above the optimal range.…”
mentioning
confidence: 99%